Densification behaviour analysis of ZrO2 nanopowders for dental applications compacted by magnetic pulsed compaction - Park, Hyo-Young; Kilicaslan, M. Fatih; Hong, Soon-Jik (Elsevier BV, 2013)
Abstract Sintered bulks of commercial ZrO 2 nanopowders were produced by combined application of magnetic pulsed compaction (MPC) and subsequent two-step sintering, and finally, their density, hardness, shrinkage and formability were analyzed. The formability tests were conducted by a CAD/CAM system. Nearly fully dense (∼98%) commercial ZrO 2 bulks were successfully obtained. With increasing MPC pressure, there was a decrease in the grain size of zirconia block. The ratio of PVA did not have a remarkable effect on the grain size. The optimum compaction pressure during MPC was 1 GPa and mixing conditions included using 1.0 wt. % PVA. The optimum processing condition included MPC process, followed by two-step sintering (first at 1000 and then at 1450 °C). The bulk under these conditions was found to have good formability, ∼97% density, reasonable hardness (1150 Hv) and ∼19% shrinkage.